Demokrasi lokal : perubahan dan kesinambungan nilai-nilai budaya politik lokal di Jawa Timur, Sumatera Barat, Sulawesi Selatan dan Bali - Zuhro, R. Siti. (Yogyakarta : Penerbit Ombak, 2009)
Continuity and change of democracy and political culture in Jawa Timur, Sumatera Barat, Sulawesi Selatan, and Balin ; research report.
Includes bibliographical references (p. 278-287) and index.
Keywords: Democracy -- Indonesia; Indonesia -- Politics and government